PENGAMATAN KESEGARAN PADA IKAN MUJAIR - Sulthan Haz Syafiq Mubarok (AGROTERAP : Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2021)
Method of catching, type and size of fish, movement of fish, weather and condition of fish before catching are factors that affect fish freshness. Fish freshness can be determined physically (organoleptic/sensory), physically and microbiologically. The decline in fish quality can be seen from the speed of entering the rigor mortis phase. The rigor mortis phase is the process of convulsing the organs in the fish's body due to the flow of oxygen in the fish's body tissues. Fish that move quickly and fish that are "sick" enter the rigor mortis phase and decay more quickly. Post-harvest handling greatly determines the freshness or quality of aquatic commodities. One of the postharvest handling that is often applied is cooling and freezing.